Two cases of spontaneous rupture of an umbilical hernia, a rare complication of portal hypertension - Peter R Oosterwijk; Eva Kouw; Wouter H. de Vos tot Nederveen Cappel (Archives of Clinical Gastroenterology - Peertechz Publications, 2017)
Portal hypertension is a severe complication of liver cirrhosis frequently leading to formation of ascites. We describe two patients that presented with a spontaneous rupture of an umbilical hernia, a rare complication of liver cirrhosis. Umbilical hernia itself however is a common complication of portal hypertension occurring in about 20% of the patients. In general, umbilical hernias in patients with liver cirrhosis warrant elective surgical repair, in a center of expertise with liver cirrhosis, after optimal management of ascites.